2019
DOI: 10.26650/eor.201972917418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of newly formed microcracks after instrumentation using Protaper Next, Reciproc and Self-Adjusting File systems

Abstract: Purpose: The purpose of the present study is to assess the rate of newly formed microcracks comparatively during root canal instrumentation by using ProTaper Next, Reciproc, and Self-Adjusting File systems using micro-computed tomography. Subjects and methods: Thirty mesial roots of mandibular molars were randomly assigned to 3 experimental groups (n = 10) as follows, ProTaper Next, Reciproc and Self-Adjusting File system. Preoperative and postoperative scans were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In a recent study, the apical occurrence of dentinal defects was investigated at three working lengths: short canal preparation (apical foramen −1 mm), at the apical foramen and over preparation (apical foramen +1 mm), and no new microcracks were created (Belladonna et al, 2021). Notwithstanding the similar findings of most publications, some micro‐CT studies reported the development of new microcracks after root canal preparation (Aggarwal et al, 2021; Alkahtany & Al‐Madi, 2020; Çakici et al, 2019; Ceyhanli et al, 2016; Jain et al, 2018; Jamleh et al, 2015, 2021; Mandava et al, 2018; Tsenova‐Ilieva et al, 2019; Table 2). The explanation for these dissimilar findings is addressed later on in this review.…”
Section: Reviewmentioning
confidence: 57%
See 3 more Smart Citations
“…In a recent study, the apical occurrence of dentinal defects was investigated at three working lengths: short canal preparation (apical foramen −1 mm), at the apical foramen and over preparation (apical foramen +1 mm), and no new microcracks were created (Belladonna et al, 2021). Notwithstanding the similar findings of most publications, some micro‐CT studies reported the development of new microcracks after root canal preparation (Aggarwal et al, 2021; Alkahtany & Al‐Madi, 2020; Çakici et al, 2019; Ceyhanli et al, 2016; Jain et al, 2018; Jamleh et al, 2015, 2021; Mandava et al, 2018; Tsenova‐Ilieva et al, 2019; Table 2). The explanation for these dissimilar findings is addressed later on in this review.…”
Section: Reviewmentioning
confidence: 57%
“…Currently, our digital search revealed 27 confirmatory studies using micro‐CT imaging technology to evaluate the frequency of dentinal microcracks after root canal preparation in extracted/stored teeth published in peer‐reviewed journals from research groups worldwide (Table 2). Eighteen of them found no new dentinal microcracks (Arumugam & Yew, 2021; Bayram et al, 2017a, 2017b; Belladonna et al, 2021; Cassimiro et al, 2017; De‐Deus et al, 2014, 2015, 2016, 2017c; Martins et al, 2021; Miguéns‐Vila et al, 2021; de Oliveira et al, 2017a, 2017b; Rödig et al, 2019; Stringheta et al, 2019; Ugur Aydin et al, 2019; Vieira et al, 2020; Zuolo et al, 2017), whilst nine studies reported the development of new defects after canal preparation (Aggarwal et al, 2021; Aksoy et al, 2019; Alkahtany & Al‐Madi, 2020; Çakici et al, 2019; Ceyhanli et al, 2016; Jain et al, 2018; Jamleh et al, 2021; Mandava et al, 2018; Tsenova‐Ilieva et al, 2019).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The main aim of endodontic therapy is to clean and fill the RCS in order to preserve or regain the integrity of the periapical tissues [45]. Despite continuous developments in instruments to improve RCS cleaning [46], dentin microcracks continue to be a source of concern for clinicians and researchers [47,48] as they often contribute to the instrumented tooth fracturing and extraction [49][50][51]. Although, there are multiple factors that contribute to dentinal crack formation like the design of the file, flexibility of file, and stress on the tooth surface used during instrumentation.…”
Section: Discussionmentioning
confidence: 99%